Breeding Programme Development of Bali Cattle at Bali Breeding Centre - Supriyantono, A; Hakim, L; Suyadi, Suyadi; Ismudiono, Ismudiono (ANIMAL PRODUCTION, 2011)
Growth performance of Bali cattle has been a major concern especially in the character of body weight at a certain age, birth weight and weaning weight.Â  Efforts to increase the quality of the performance of Bali cattle have been carried out by the government by forming P3Bali. In the activities of quality improvement, the government is guided by the breeding program which has been prepared. To strengthen these activities further, the breeding program has been modified based on weaning weight data for 10 years (1994-2004). Data were analyzed using the VCE and PEST to estimate the components of genetic variance and covariance. The breeding program was set up based on the results of the accuracy of some methods of selection. The results showed that the ratio of male to female optimum (1:5) would increase the selection response per generation about 53.08 percent. Selection responses were obtained when males were maintained for three years and females over six years in the population. (Animal Production 13 (1):45-51 (2011)Key Words: Bali cattle, breeding program, selection response